2018
DOI: 10.1002/cctc.201701366
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Borrowing Alcohol Bioamination with Coimmobilized Dehydrogenases

Abstract: The amination of alcohols is an important transformation in chemistry. The redox-neutral (i.e., hydrogen-borrowing) asymmetric amination of alcohols is enabled by the combination of an alcohol dehydrogenase (ADH) with an amine dehydrogenase (AmDH). In this work, we enhanced the efficiency of hydrogen-borrowing biocatalytic amination by co-immobilizing both dehydrogenases on controlled porosity glass FeIII ion-affinity beads. The recyclability of the dual-enzyme system was demonstrated (5 cycles) with total tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 51 publications
2
54
1
Order By: Relevance
“…Biocatalytic methods have emerged as a sustainable solution for the synthesis of chiral amines by means of the single action of enzymes of several classes, including lipases, amine transaminases (ATAs), amine oxidases, amine dehydrogenases, imine reductases or reductive aminases, but, interestingly, great efforts have in recent years been devoted to the synthesis of chiral amines through chemo‐, photo‐ and multienzymatic approaches . As an example, the selective amination of racemic sec ‐alcohols through elegant cascades based on the combination of alcohol‐dehydrogenase‐catalysed oxidation to ketones with subsequent bioamination by using ATAs or amine dehydrogenases has been described. In spite of these efforts, the biocatalytic synthesis of (3 E )‐4‐arylbut‐3‐en‐2‐amines has received little attention, the activity of commercially available amine transaminases for the bio‐transamination of (3 E )‐4‐phenylbut‐3‐en‐2‐one into optically active (3 E )‐4‐phenylbut‐3‐en‐2‐amine being low (<30 %) …”
Section: Introductionmentioning
confidence: 99%
“…Biocatalytic methods have emerged as a sustainable solution for the synthesis of chiral amines by means of the single action of enzymes of several classes, including lipases, amine transaminases (ATAs), amine oxidases, amine dehydrogenases, imine reductases or reductive aminases, but, interestingly, great efforts have in recent years been devoted to the synthesis of chiral amines through chemo‐, photo‐ and multienzymatic approaches . As an example, the selective amination of racemic sec ‐alcohols through elegant cascades based on the combination of alcohol‐dehydrogenase‐catalysed oxidation to ketones with subsequent bioamination by using ATAs or amine dehydrogenases has been described. In spite of these efforts, the biocatalytic synthesis of (3 E )‐4‐arylbut‐3‐en‐2‐amines has received little attention, the activity of commercially available amine transaminases for the bio‐transamination of (3 E )‐4‐phenylbut‐3‐en‐2‐one into optically active (3 E )‐4‐phenylbut‐3‐en‐2‐amine being low (<30 %) …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our research group and other groups have shown that a large excess of a (ca. 0.2–1 m ) is required to drive the reductive amination of ketone substrates (15–50 m m ) in aqueous buffer to a significant extent . Moreover, AmDHs, such as Ch1‐AmDH, have a K M value of about 1 m for a .…”
Section: Resultsmentioning
confidence: 74%
“…This is not a simple matter, as most ADHs are highly enantioselective. More recently, the efficiency of the direct asymmetric amination of a secondary alcohol was improved by co‐immobilization of the ADH and AmDH …”
Section: The Current Biocatalysis Landscapementioning
confidence: 99%